1988
DOI: 10.1159/000212942
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the P<sub>300</sub> Auditory Event-Related Potential and Automated Psychometric Tests

Abstract: Event-related potentials particularly the P3 component have been noted to be abnormal in illnesses affecting cognitive processes, such as dementia. The relationship between the P3 latency and objective tests of mental function in patients with Alzheimer’s disease and vascular dementia has been studied. A significant correlation was demonstrated between P3 latency and automated psychometric tests in patients with Alzheimer’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…This is a surprising finding since computerised psychometric tests are said to have several advantages over subjective tests and, in particular, they are said to (a) ensure that material is presented in a standardised form to all subjects and (b) more importantly, minimise the experimenter's bias. Our own previous studies have shown that results obtained on the automated tests correlate well with not only the latency values for P300 (Wright et al, 1988) but with the results obtained on the MMSE (Rai and Scott, 1989). It may be argued by some that the lack of detectable and significant decline in function over time noted in the results of P300 and the automated psychometric tests may represent increased variability of results of these tests with time in the elderly.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is a surprising finding since computerised psychometric tests are said to have several advantages over subjective tests and, in particular, they are said to (a) ensure that material is presented in a standardised form to all subjects and (b) more importantly, minimise the experimenter's bias. Our own previous studies have shown that results obtained on the automated tests correlate well with not only the latency values for P300 (Wright et al, 1988) but with the results obtained on the MMSE (Rai and Scott, 1989). It may be argued by some that the lack of detectable and significant decline in function over time noted in the results of P300 and the automated psychometric tests may represent increased variability of results of these tests with time in the elderly.…”
Section: Discussionsupporting
confidence: 72%
“…Patients and normal volunteers were divided into two groups because (a) all these assessments involved cooperation from an individual for a period exceeding one and half hours and (b) some volunteers indicated that they would only like to be assessed once a year. Group I (10 patients with SDAT and 10 normal elderly) were followed up at yearly intervals and assessed using Downloaded by [Central Michigan University] at 03:54 03 January 2015 76 CLJNICAL GERONTOLOGIST the MMSE, Kendrick cognitive tests and two computerised automated tests, as described in our earlier paper (Wright et al, 1988). Group I1 (5 patients with SDAT and 5 normal elderly) were followed up at three monthly intervals and assessed using MMSE and P300 latency.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, there is a need for combined assessment tools which can improve the early diagnosis of dementia (Rachakonda et al, 2004; Dickerson et al, 2007; Dubois et al, 2007; Burns and Morris, 2008; Albert et al, 2011; Jack Jr. et al, 2011; Sperling et al, 2011). Event Related Potentials (ERPs), particularly the P300 wave, has proved to be sensitive to the early effects of AD (Muir et al, 1988; St Clair et al, 1988; Wright et al, 1988; Polich, 1989; Pokryszko-Dragan et al, 2003; Katada et al, 2004; Polich and Corey-Bloom, 2005; Ally et al, 2006; Bonanni et al, 2010; Lai et al, 2010). Using the classical odd-ball paradigm (Sutton et al, 1965) the characteristics of the P300 wave that have proved most useful in experimental and clinical settings are its amplitude and latency.…”
Section: Introductionmentioning
confidence: 99%
“…The p AD patients were also required for the controlled evaluation of surgery‐related effects on cognition. As the main outcome measure, we chose event‐related P300 potentials 9,12 because these brain potentials appear to sensitively reflect clinically important aspects of human information‐processing functions in various conditions (e.g., cognitive development 13,14 intoxications 15,16 pharmacological challenge 17,18 and therapy studies 19 metabolic encephalopathies, 22 multiple cerebral infarcts 23–24 and dementia 25,28 …”
mentioning
confidence: 99%